HYDRODYNAMIC STUDIES ON LIQUID-LIQUID TWO PHASE FLOW SEPARATION IN MICROCHANNEL BY CFD MODELLING - CUI TING, CHUE (IRC, 2017)
Microfluidic systems undergo rapid expansion of its application in different industries over the few decades. Industries have exploited its surface tensiondominated property to achieve better mixing and improve mass transfer between two immiscible liquids. Rapid separation is needed for many reactions that required precise residence time, to enhance production yield. The separation technique for two-phase fluid flow in microfluidic system is different from the macro-system, as the gravitational force is overtaken by surface force. To understand these phenomena completely, a study on the hydrodynamic characteristics of two-phase oil-methanol system in polydimethylsiloxane (PDMS) microchannel is carried out. The objective of this work is to separate the products from a transesterification process of oil and methanol. A multiphase Volume of Fluid (VOF) model is developed to predict the fluid flow in microchannel. An inline separator design is proposed along with its variable to obtain effective separation for the oil-methanol system. The separation performance is evaluated based on the amount of oil recovered and its purity